Sustainable construction : green building design and delivery - Kibert, Charles J. (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
The classic reference for high-performance green building delivery systems. No longer just a buzzword, sustainable construction is going mainstream$1 (Band soon will be the norm. Revised to reflect the latest developments of the U.S. Green Building Council's Leadership in Energy and Environmental Design (LEED) rating system and other tools, Sustainable Construction: Green Building Design and Delivery, Third Edition guides construction and design professionals through the process of developing commercial and institutional high-performance green buildings in today's marketplace. Charles Kibert provides an introduction to green building, covering the theory, history, and state of the industry as well as best practices in building procurement and delivery systems. From green building and Green Globes assessments to building hydrological systems and materials and product selection, this comprehensive text covers all of the factors involved with sustainable construction. In a clear and accessible writing style, Kibert addresses issues so that the reader can think critically and independently as part of the cutting edge in green building. The Third Edition includes up-to-date coverage of: The latest developments leading up to LEED version 4 Carbon neutral design and carbon accounting Green Globes and international building assessment systems The Living Building Challenge Environmental product declarations (EPDs) as the norm for green building products The trends in net-zero energy building design and policies Broad enough to cover the needs of faculty and students and detailed enough to serve as a professional reference, Sustainable Construction, Third Edition is a must for the builder/owner and construction manager looking to take advantage of the opportunities in this rapidly evolving field, the designer looking to be LEED certified, or anyone interested in sustainability-- Amazons